Continuing Vocational Training in Enterprises: Comparison of Selected Indicators of the Czech Republic and Hungary - Michelini, David; Kristl Volfová, Monika (GILE Journal of Skills Development, 2024)
This article presents a comparative analysis of Continuing Vocational Training (CVT) in companies in the Czech Republic and Hungary based on selected indicators from the European Union's CVT survey. The study examines the participation of employees, the time dedicated to training, and the primary targeted skills of CVT courses. The results highlight significant differences in participation rates and focus on specific skills between the two countries, with a higher percentage of employee participation in training in the Czech Republic and a particular focus on IT skills in Hungary. The findings suggest that CVT plays a crucial role in enhancing employee skills and organizational competitiveness, highlighting the need to explore further the reasons behind these differences between countries and their impact on policy and practice in vocational education. The study also emphasizes the importance of adapting CVT programs to the rapidly changing labor market and the employer's need to effectively respond to new challenges in skills and competencies.